A atuação do STF no reconhecimento dos “crimes de lesa-humanidade” e a justiça de transição - Vilar, Suyane Alves de Queiroga (2019)
The affirmation of human rights after the Universal Declaration of Human Rights of 1948 began to be thought from a new paradigm: the idea of human dignity as central axis of social relations, being this new order, protected by international systems with global and regional formation. In Brazil, some international treaties and norms have been ratified about the matter, in order to guarantee and standardize the protection of human rights. However, there is a divergence between what is legally applied in the Inter-American Court of Human Rights and what is understanding postulated by the Federal Supreme Court. Thus, as research problem, questioned the extent to wich the STF's understanding diverges from the jurisprudence of the Inter-American Court of Human Rights, regarding individual responsibility for the practice of "crimes against humanity" by state agents? How does the STF decision on the interpretation of the Amnesty Law affect the inapplicability of individual accountability of perpetrators of violence during periods of military dictatorship? Considering what would be International Human Rights Law and Transitional Justice, its effects and results, as well as the various public policies to rescue the memory and knowledge of history during the period of military arbitration in the consolidation of a democracy was investigated the reflexes of the understanding formulated by the STF on "crimes against humanity" and the Amnesty Law of Brazil. The work that follows, was developed through the qualitative approach using the dialectical method, through bibliographical and documentary research. The literature used approached interdisciplinary theoretical frameworks of Law, History, Political Science and Sociology. And, with the help of the case study, it was possible to describe the theme of "crimes against humanity" based on the right to memory and truth, through the method of historical procedure. As a technique of analysis, the method of construction of the explanation was used to understand the effects of the decisions of the STF judges, which are set out in the processes that are cut before the individual responsibility of the perpetrators of violence, not to work for the recognition of "crimes against humanity” within the historical context to which the events were inserted